Impact of the secondary plant metabolite Cucurbitacin B on the demographical traits of the melon aphid, Aphis gossypii. Issue 1 (December 2018) - Yousaf, Hafiz; Shan, Tisheng; Chen, Xuewei; Ma, Kangsheng; Shi, Xueyan; Desneux, Nicolas; Biondi, Antonio; Gao, Xiwu
Abstract Cucurbitacin B is a natural triterpene present in plants of Cucurbitaceae family, which are among the host plants for melon aphid, Aphis gossypii . In present study we characterized the effects of two cucurbitacin B concentrations on the biological parameters of adults (F0 ) and of juveniles and adults of their progeny (F1 ). The results showed that cucurbitacin B at 25 ppm significantly reduced the adult longevity and fecundity of both F0 and F1 generation. Exposure of F0 generation to 25 ppm though reduced the demographic traits of F1 including the intrinsic rate of increaser (day−1 ), generation timeT (day), finite rate of increaseλ (day−1 ), however, only net reproductive rateR 0 (offspring/individual) decreased significantly. While 100 ppm reduced not only the longevity and fecundity of F0 generation but also the longevity of F1 generation. Fecundity of F1 was not affected by 100 ppm of cucurbitacin B, however, R 0 (offspring/individual) andT (day) of F1 generation were lower than the control population. These results support the hypothesis that high contents of cucurbitacin B caused negative impact on melon aphid and could be used as a lead for classical selection of resistant varieties of plants that are main hosts for the melon aphid.